Self assembled structures for 3D integration - Rao, Madhav (ProQuest Dissertations & Theses, 2012)
Three dimensional (3D) micro-scale structures attached to a silicon substrate have various applications in microelectronics. However, formation of 3D structures using conventional micro-fabrication techniques are not efficient and require precise control of processing parameters. Self assembly is a method for creating 3D structures that takes advantage of surface area minimization phenomena. Solder based self assembly (SBSA), the subject of this dissertation, uses solder as a facilitator in the formation of 3D structures from 2D patterns. Etching a sacrificial layer underneath a portion of the 2D pattern allows the solder reflow step to pull those areas out of the substrate plane resulting in a folded 3D structure. Initial studies using the SBSA method demonstrated low yields in the formation of five different polyhedra. The failures in folding were primarily attributed to nonuniform solder deposition on the underlying metal pads. The dip soldering method was analyzed and subsequently refined. A modified dip soldering process provided improved yield among the polyhedra. Solder bridging referred as joining of solder deposited on different metal patterns in an entity influenced the folding mechanism. In general, design parameters such as small gap-spacings and thick metal pads were found to favor solder bridging for all patterns studied. Two types of soldering: face and edge soldering were analyzed. Face soldering refers to the application of solder on the entire metal face. Edge soldering indicates application of solder only on the edges of the metal face. Mechanical grinding showed that face soldered SBSA structures were void free and robust in nature. In addition, the face soldered 3D structures provide a consistent heat resistant solder standoff height that serve as attachments in the integration of dissimilar electronic technologies. Face soldered 3D structures were developed on the underlying conducting channel to determine the thermo-electric reliability of face soldered structures.